2022
DOI: 10.1097/md.0000000000029656
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of different acupuncture therapies for neck pain

Abstract: Background: Neck pain is a common musculoskeletal symptom that has negative effects on quality of life and work productivity. Acupuncture has been widely used for neck pain, and a number of randomized controlled trials (RCTs) and systematic reviews (SRs) have evaluated its effectiveness. However, previous studies have obtained inconsistent results regarding the effects of acupuncture for neck pain, and there is no SR for the comparative efficacy and safety of various types of acupuncture. Therefore, we herein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…A recent meta-analysis indicated that electroacupuncture was more effective than other interventions (usual care, sham acupuncture or no treatment) in reducing pain and disability index scores. 35 Similarly, several other reviews support acupuncture’s role in treating neck pain, highlighting its potential as a non-pharmacological treatment option. 36 37 For the treatment of acute phase, prioritising simple and straightforward procedures is essential.…”
Section: Discussionmentioning
confidence: 98%
“…A recent meta-analysis indicated that electroacupuncture was more effective than other interventions (usual care, sham acupuncture or no treatment) in reducing pain and disability index scores. 35 Similarly, several other reviews support acupuncture’s role in treating neck pain, highlighting its potential as a non-pharmacological treatment option. 36 37 For the treatment of acute phase, prioritising simple and straightforward procedures is essential.…”
Section: Discussionmentioning
confidence: 98%
“…Chronic non-specific low back pain, one of the most common conditions in orthopaedics, rehabilitation, and pain medicine, accounts for 1/3 ( Wang et al, 2015 ) of daily outpatient visits, and is a major cause of increase in years of life lived with disability, in both developed and developing countries ( Diseases and Injuries, 2020 ). Recently, evidence has been published for ACE being beneficial in relieving pain from patients ( Jo et al, 2022 ). However, the evidence for clinical studies targeting ACE in CNLBP treatment is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a growing body of clinical evidence supports the use of ACE for the management of painful conditions. For example, a meta-analysis showed that ACE is beneficial for the relief of neck pain ( Jo et al, 2022 ). However, to our knowledge, no clinical study on ACE for the treatment of CNLBP has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A Korean survey on the effects of AEM on neck pain showed that AEM alleviated the pain, reduced disability index scores, and showed higher efficacy rate compared to control. [ 27 ] Moreover, in patients with carpal tunnel syndrome Korean method of AEM showed remarkable effects on finger tingling, Phalen test, and pain severity. [ 11 ] Mexican TCM scientists compared the effects of AEM with fluoxetine in depressed rat model and showed antidepressant effects of AEM and its potential to remodel the hippocampus.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%